Peat pellets as adsorbent for petrol's volatile organic compounds emission - Hazwanee Osman, 1987-; Mohd. Shahru Bahari; Fakulti Sains (2008)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2008